Criterion validity and test-retest reliability of SED-GIH, a single item question for assessment of daily sitting time - Kristina Larsson; Lena V. Kallings; Örjan Ekblom; Victoria Blom; Eva Andersson; Maria M. Ekblom (BMC, 2019)
Abstract Background Sedentary behaviour has been closely linked to metabolic and cardiovascular health and is therefore of importance in disease prevention. A user-friendly tool for assessment of sitting time is thus needed. Previous studies concluded that the present tools used to assess a number of sedentary behaviours are more likely to overestimate sitting than single-item questions which often underestimate sitting time, and that categorical answering options are recommended. In line with this, the single-item question with categorical answering options, SED-GIH, was developed. The aim of this study was to investigate the criterion validity of the SED-GIH question using activPAL3 micro as the criterion measure. The second aim was to evaluate the test-retest reliability of the SED-GIH questionnaire. Method In the validity section of this study, 284 middle-aged adults answered a web questionnaire, which included SED-GIH, wore activPAL and filled in a diary log for one week. Spearman's rho assessed the relationship between the SED-GIH answers and the daily average sitting time as monitored by the activPAL (activPAL-SIT), a Weighted Kappa assessed the agreement, ANOVA assessed differences in activPAL-SIT between the SED-GIH answer categories, and a Chi2 compared the proportions of hazardous sitters between the different SED-GIH answer categories. In the reliability section, 95 elderly participants answered the SED-GIH question twice, with a mean interval of 5.2 days. The reliability was assessed with ICC and a weighted Kappa. Results The SED-GIH question correlated moderately with activPAL-SIT (rho = 0.31), with a poor agreement (weighted Kappa 0.12). In total, 40.8% underestimated and 22.2% overestimated their sitting time. The ANOVA showed significant differences in activPAL-SIT between the different SED-GIH answer categories (p < 0.001). The Chi2 showed a significant difference in proportion of individuals sitting more than 10 h per day within each SED-GIH answer category. ICC for the test-retest reliability of SED-GIH was excellent with ICC = 0.86, and the weighted Kappa showed an agreement of 0.77. Conclusions The unanchored single item SED-GIH question showed excellent reliability but poor validity in the investigated populations. Validity and reliability of SED-GIH is in line with other questionnaires that are commonly used when assessing sitting time.